2011
DOI: 10.1186/1471-2164-12-572
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of Flustra foliacea (Ectoprocta, Cheilostomata) - compositional bias affects phylogenetic analyses of lophotrochozoan relationships

Abstract: BackgroundThe phylogenetic relationships of the lophophorate lineages, ectoprocts, brachiopods and phoronids, within Lophotrochozoa are still controversial. We sequenced an additional mitochondrial genome of the most species-rich lophophorate lineage, the ectoprocts. Although it is known that there are large differences in the nucleotide composition of mitochondrial sequences of different lineages as well as in the amino acid composition of the encoded proteins, this bias is often not considered in phylogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 76 publications
(104 reference statements)
1
14
0
Order By: Relevance
“…Similar to previous report, AT-Skew and GC-skews usually show high levels of variation, indicating the effects of phylogenetic analyses (Nesnidal et al 2011). The nucleotide skewness for the coding strands of T. acus melanotus (GC-skew ¼ À0.21, AT-skew ¼0.02) is biased towards A and C. A similar trend has been observed in other teleost mitogenomes: the negative GC-skew ranges from À0.53(ATP8) to À0.12(CO2) and the AT-skew showed more positive varying from À0.17(ND3) to 0.26(ATP6).…”
supporting
confidence: 90%
“…Similar to previous report, AT-Skew and GC-skews usually show high levels of variation, indicating the effects of phylogenetic analyses (Nesnidal et al 2011). The nucleotide skewness for the coding strands of T. acus melanotus (GC-skew ¼ À0.21, AT-skew ¼0.02) is biased towards A and C. A similar trend has been observed in other teleost mitogenomes: the negative GC-skew ranges from À0.53(ATP8) to À0.12(CO2) and the AT-skew showed more positive varying from À0.17(ND3) to 0.26(ATP6).…”
supporting
confidence: 90%
“…Samples were sequenced using the Illumina HiSeq 2000 platform (Illumina, San Diego, CA, USA), following the protocols supplied by Illumina. Reads were assembled using ABySS (kmer ¼ 30; Simpson et al 2009), and the contigs were then aligned with BLAST using the database of seven reported bryozoan mitochondrial genomes (Waeschenbach et al 2006;Jang and Hwang 2009;Sun et al 2009;Nesnidal et al 2011;Sun et al 2011;Shen et al 2012;Waeschenbach et al 2012). The largest matched contig is 15 101 bp in length.…”
Section: Sequencing Using Illumina Hiseq 2000mentioning
confidence: 99%
“…With the mitochondrial genome sequence of B. neritina from China (QD), the currently available eight bryozoan mitochondrial genomes from GenBank were included in the phylogenetic analysis, including B. neritina from China (TG) (Jang and Hwang 2009), Celleporella hyalina (Waeschenbach et al 2012), Flustra foliacea (Nesnidal et al 2011), Flustrellidra hispida (Waeschenbach et al 2006), Membranipora grandicella (Shen et al 2012), Tubulipora flabellaris and Watersipora subtorquata ). In addition, 10 genera of Lophotrochozoa with at least two complete mitochondrial genomes reported, including Mytilus, Crassostrea, Hyriopsis, Meretrix, Sepiella, Aplysia, Potamopyrgu, Conus, Haliotis and Sypharochiton, were also incorporated in the analysis.…”
Section: Genetic Distance and Phylogenetic Analysis Within Lophotrochmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that changes in the mitochondrial gene order can be used as cladistic characters for studying relationships among higher-level taxa [ 3 ]. In some taxonomic groups such as insects and vertebrates the gene order tends to be conservative, while in some other groups such as Mollusca [ 4 ], Bryozoa [ 5 7 ], Acari [ 8 ], and Tunicata [ 9 , 10 ] it is highly variable. Generally, the taxon-specific gene order remains identical over long periods of time [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%